Changes in the spatial distribution of erosion within a selectively logged rainforest catchment in Borneo 1988-2003 - Walsh, Rory Peter Dominic; Clarke, Michelle A.; Kawi Bidin; Blake, William H.; Chappe, N. A.; Douglas, Ian; N. Ramli; Aimée M. Sayer; Waidi Sinun; J. Larenus; Jamal Mohd Hanapi (CABI Publishing, 2006)
[No abstract available]